Factors Affecting Satisfaction and Loyalty of Social Science Students in A Public University In Shanxi, China - Yao, Hui (Scholar: Human Sciences, 2023)
Purpose: This study aims to determine the impacting factors of satisfaction and loyalty among students majoring in social science at public universities in Shanxi Province. The conceptual framework proposes causal relationships among built environment, teaching care, university image, student trust, academic aspects, student satisfaction, and student loyalty. Research Design, Data, and Methods: A quantitative method was used to distribute questionnaires to 500 students majoring in science and technology at the Taiyuan Institute of Technology. The sample techniques were purposive, stratified random and convenience sampling. Before the data collection the Item Objective Congruence (IOC) and Cronbach’s alpha were used to test to ensure the validity of the content. Confirmatory factor analysis (CFA) was used to analyze the data, including model fit, reliability, and validity. Structural equation modeling (SEM) was conducted to test hypotheses. Results: The built environment has a significant influence on student satisfaction and teaching care. The built environment, teaching care, university image, student trust, and academic aspects significantly affect student satisfaction toward loyalty. Conclusion: The results implied that universities could pay attention to their strategic development to improve the facilities, student relationship, university image, academic aspects, and trust, which will help to enhance students’ satisfaction and loyalty.